Penguatan Kesadaran Hukum Komunitas melalui Sosialisasi Pencegahan Peredaran Narkotika di Desa Penujak, Lombok Tengah, Indonesia - Ahwan, Ahwan; Lalu Panca Tresna D; Muhammad Rifaldi Setiawan; Ayang Afira Anugerahayu; Yuni Ristanti (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
The illegal distribution of narcotics has spread to rural areas. This poses a serious threat not only to the development of the younger generation in villages, but also to the conduciveness and homeostasis of values upheld by rural communities. Responding to growing concerns about this issue, academic intervention in the form of socialization and legal counseling related to the circulation and dangers of narcotics has become an urgent need. This became the basis for the implementation of community service activities with the topic "Strengthening Community Legal Resilience through Socialization of Narcotics Circulation Prevention". This activity took place in Penujak Village, Central Lombok Regency. In line with the topic, this activity aimed to construct community legal resilience as an intervention compatible with the character of the village community. The activity began with an initial mapping of the village community's understanding through Focus Group Discussions (FGD) and interviews. The results of this mapping were then used as material for the preparation of the socialization material. The activity was very well received by the Penujak Village community, most importantly because it provided the community with additional understanding regarding the illegal distribution of narcotics. The results of the mapping were then used as material for the preparation of outreach materials. This activity was very well received by the community of Penujak Village, most importantly because it increased the community's understanding of the illegal distribution of narcotics. The final evaluation results showed that the community finally understood various things, such as the reporting mechanism and important substances covered by various regulations related to narcotics in Indonesia.